Ports in the Medieval European Atlantic : shipping, transport and labour - Rivera Medina, Ana Ma. (Ana María) (The Boydell Press, 2021)
Presents a wealth of original research findings on how medieval ports actually worked, providing new insights on shipping, trade, port society and culture, and systems of regional and international integration.